Pengaruh Model Pembelajaran Problem Based Learning Berbasis TPACK terhadap Keterampilan Bertanya Siswa pada Mata Pelajaran Biologi Materi Sel Kelas XI MAN 2 Samarinda - Ramadhani, Khairunnisa Salsabila; Masitah, Masitah; Herliani, Herliani; Serena, Nelda Anasthasia; Akhmad, Akhmad (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
The background of this research is learning models that are limited in variation, which makes the students less active, especially in questioning skills. Because of that, this research has a purpose to find out the effect of implementing the Problem Based Learning (PBL) model based on Technological Pedagogical and Content Knowledge (TPACK) on students questioning skills. This research used a quantitative approach with a quasi experimental method and a non- equivalent control group design. The subjects of this research are 70 grade XI students in MAN 2 Samarinda, including class XI-B as the experimental class and class XI-A as the control class. The instruments used in this research are interviewing the teacher, observing the learning activities, and an assessment rubric of students questioning skills. The results of this research showed that students questioning skills in the experimental class increased significantly compared to the control class, as shown by the Mann-Whitney U test with a significance value of 0.015 < 0.05. The number of questions from students in the experimental class was more varied (20 questions) compared to the control class, which had fewer questions (5 questions). The conclusion is that the implementation of the TPACK based Problem Based Learning (PBL) model has a positive effect on students questioning skills in the cell material of Grade XI.